A cell fitness selection model for neuronal survival during development - Yiqiao Wang (Nature Portfolio, 2019)
Programmed cell death is an important part of tissue development, and traditionally it is considered that neuronal death is a stochastic process in response to neurotrophic factor deprivation. Here the authors show that for TrkC+ proprioreceptors, which neurons die is predetermined molecularly by how much TrkC is present, as well as by a gene expression signature.